The Chemical Structure Properties and Promoting Biofilm Activity of Exopolysaccharide Produced by Shigella flexneri - Song, Yinglong; Ma, Fenglian; Sun, Mengying; Mu, Guangqing; Tuo, Yanfeng (Frontiers in Microbiology, 2022)
Shigella flexneri is a waterborne and foodborne pathogen, can damage human health. The exopolysaccharides (S-EPS) produced by Shigella flexneri CMCC51574 were found to promote biofilm formation and virulence. In this research, the crude S-EPS produced by Shigella flexneri CMCC51574 were separated into three main different fractions, S-EPS 1-1, S-EPS 2-1, and S-EPS 3-1. The structure of the S-ESP 2-1 was identified by FT-IR, Ion Chromatography analysis, Methylation analysis, and NMR analysis. The main chain of S-EPS 2-1 was α-Manp-(1→3)-α-Manp-[(1→2,6)-α-Manp]15-[(1→2)-Manf-(1→]8, there were two branched-chain R1 and R2 with ratios 4:1, R1: α-Manp-(1→6)- and R2: α-Manp-(1→6)- Glc-(1→6)- were linked with (1→2,6)-α-Manp. And it was found that S-EPS 2-1 exhibited the highest promoting effect on biofilm formation of S. flexneri. The S-EPS 2-1 was identified to interact with extracellular DNA (eDNA) of S. flexneri, indicating that the S-EPS 2-1 was the specific polysaccharide in the spatial structure of biofilm formation. Our research found the important role of S-EPS in S. flexneri biofilm formation, which will help us to understand the underlining mechanisms of the biofilm formation and find effective ways to prevent S. flexneri biofilm infection.